Understanding ferroelectricity in layered perovskites: new ideas and insights from theory and experiments. Issue 23 (21st June 2015) - Benedek, Nicole A.; Rondinelli, James M.; Djani, Hania; Ghosez, Philippe; Lightfoot, Philip
<x xml:space="preserve">Abstract</x> Recent theoretical and experimental studies showing how polar structures or ferroelectricity arise in layered perovskites are highlighted.